2018
DOI: 10.3390/w10060768
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Agricultural Water Pricing in an Irrigation District Based on a Bayesian Network

Abstract: In recent years, the large-scale development of land and water resources has led to a conflict between water supply and demand. Especially in arid regions, fragile ecosystems and continuous farmland expansion have threatened the ecological and social security of river basins. Therefore, it is urgent to propose scientific and reasonable water resource management models to alleviate this conflict. Based on the principle of "the strictest water resource management measures" for river basin water resources, this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…In addition, they may allow harvesting of two crops per year, leading to higher benefits than in other areas, largely due to the increased VP (Johnson et al., 2017). Costs also show high geographical variation; for example, the water opportunity costs tend to be high in areas with insufficient water, such as China's arid and semi‐arid northern areas (Zhu et al., 2018). For example, Tianjin is a coastal city, with a relatively mild climate and lower ecological protection costs, and it is possible to grow two crops annually.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they may allow harvesting of two crops per year, leading to higher benefits than in other areas, largely due to the increased VP (Johnson et al., 2017). Costs also show high geographical variation; for example, the water opportunity costs tend to be high in areas with insufficient water, such as China's arid and semi‐arid northern areas (Zhu et al., 2018). For example, Tianjin is a coastal city, with a relatively mild climate and lower ecological protection costs, and it is possible to grow two crops annually.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have proved the demand price elasticity as a serious limitation; Exposito and Berbel [74] concluded that water pricing policy loses effectiveness in areas characterized by water scarcity and supply restrictions, as overexploited aquifers. Although success pricing policy cases exists, Rogers et al [75] commented that integrated pricing from all sources should exist and be supplemented by other policies and indicators (environmental and social), discussed by other studies [16,54]. Providing a price for water would make the opportunity cost of water explicit to farmers, which could lead them to changes in selecting crops, and could incentivize the participation in the water market during drought.…”
Section: Discussionmentioning
confidence: 99%
“…Modeling methods, either inductive or deductive [13], have proven to be a useful tool for estimating the economic value of water and its demand for irrigation use, as indicated by Tsur [14], as well as for assessing water allocation policies [15]. The use of inductive techniques including statistical methods, e.g., econometrics, applied for irrigation water value and water derived demand in agriculture, have been used in different countries, with insights for water policy applications, as can be seen in Zhu et al, Mesa-Jurado et al, and Sun et al [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The refore, a reasonable proportion of the oasis scale (i.e., 5:5-6) is beneficial in order to control agricultural water use, and to enhance the regulating ecosystem service (CAS) of natural vegetation [84]. Moreover, the application of a Bayesian network model in arid basins could promote the reduction of farmland and irrigation water by adjusting the water price, in order to ensure the scale and area of oasis areas, and to improve habitat function [85]. Through water-saving and water-retaining engineering measures, according to the actual needs of crop irrigation, the use of water-saving irrigation technology can reduce ET and other invalid losses in the process of water transfer, improve the efficiency of utilization of water resources in farmland, and promote the water cycle of the basin [50,82,83,86].…”
Section: Optimal Management Of Water Resources Based On Ecosystem Servicesmentioning
confidence: 99%